2019
DOI: 10.1016/j.colsurfa.2019.123810
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of aqueous droplets with common and superspreading surfactants. A molecular dynamics study

Abstract: The surfactant-driven spreading of droplets is an essential process in many applications ranging from coating flow technology to enhanced oil recovery. Despite the significant advancement in describing spreading processes in surfactantladen droplets, including the exciting phenomena of superspreading, many features of the underlying mechanisms require further understanding. Here, we have carried out molecular dynamics simulations of a coarse-grained model with force-field obtained from the Statistical Associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 84 publications
(143 reference statements)
2
29
0
Order By: Relevance
“…It cannot be discounted that aggregation formation may be important as the simulations were not sufficient to analyse possible differences between aggregates [21]. The diffusion dynamics of the three different types of surfactant are similar in agreement with current results from CG simulation [26], which may indicate a lesser role of diffusion dynamics for superspreading. Still, the adsorption ability of the surfactant may play a role, as has been discussed in later studies [19,20].…”
Section: All-atom Modelssupporting
confidence: 81%
See 4 more Smart Citations
“…It cannot be discounted that aggregation formation may be important as the simulations were not sufficient to analyse possible differences between aggregates [21]. The diffusion dynamics of the three different types of surfactant are similar in agreement with current results from CG simulation [26], which may indicate a lesser role of diffusion dynamics for superspreading. Still, the adsorption ability of the surfactant may play a role, as has been discussed in later studies [19,20].…”
Section: All-atom Modelssupporting
confidence: 81%
“…Most importantly, it was also found that the T-shaped surfactants undergo weaker micellisation, which may result in faster spreading [71]. The latter result has been recently corroborated by MD simulations based on the SAFT CG force-field [26].…”
Section: Martini Modelmentioning
confidence: 63%
See 3 more Smart Citations